Mother Africa Through the Ages - Ugowe, Christpher Osadiaye (Nigeria, 2010)
Against the background of the schievements, contributions and triumphs of Africa in ages past, this compelling book chronicles the history and enormity of the black man's burden in modern times, along with the challenges of contemporary Africa for her own peoples and for the rest of the world...
Keywords: African History; Non-Fiction